Índice
1
▪
▪
▪
▪
▪
𝑥(𝑡, 𝑆) 𝑆
𝛺 𝑆 ∈ 𝛺 → 𝑥(𝑡, 𝑆) ∈ ℝ 𝑡
𝑇 𝑡 ∈ 𝑇 ⊂ ℝ
𝑥(𝑡, 𝑆0) ≡ 𝑥(𝑡)
𝑅𝑀𝑆{𝑥[𝑛]} = √1
𝑁∑ 𝑥[𝑛]
𝑁−1
𝑖=0
𝑆𝑃𝐿{𝑥[𝑛]} = 20 log10 𝑅𝑀𝑆 20𝜇𝑃𝑎
𝐴𝑆{𝑥[𝑛]} =𝐸[𝑥 − 𝜇{𝑥}]3 𝜎{𝑥}3
𝜇 𝜎 𝐸[𝑦]
𝑦
𝜇
𝑦𝑖
𝑝(𝑦𝑖) 𝐸[𝑦] = ∑ 𝑦𝑖𝑝(𝑦𝑖)
𝑓
𝐹{𝑥(𝑡)} ≡ 𝑋𝐹(𝑓) = ∫ 𝑥(𝑡) · 𝑒−2𝜋𝑓𝑡𝑑𝑡
+∞
−∞
𝑆𝑥𝑥(𝑓) = | 𝑋𝐹(𝑓)|2
𝑆𝑥𝑥 𝑓
𝑥[𝑛] 𝑁
𝑥[𝑛]
𝐹{𝑥(𝑡)} ≡ 𝑋𝐹[𝑘/𝑁] =1
𝑁∑ 𝑥[𝑛] · 𝑒−2𝜋𝑛𝑘/𝑁
𝑁−1
𝑛=0
𝑆𝑀0{𝑥[𝑛]} = ∑ 𝑃𝑆𝐷𝑖
𝑁−1
𝑖=0
𝑆𝑀𝑗{𝑥[𝑛]} = ∑ 𝑃𝑖𝑓𝑖𝑗
𝑁−1
𝑖=0
𝑉𝐹𝐶{𝑥[𝑛]} =𝑆𝑀2
𝑆𝑀0− (𝑆𝑀1 𝑆𝑀0)
2
∑ 𝑃𝑆𝐷𝑖
𝑀𝐷𝐹
𝑖=0
= ∑ 𝑃𝑆𝐷𝑖
𝑁−1
𝑖=𝑀𝐷𝐹
=1
2∑ 𝑃𝑆𝐷𝑖
𝑁−1
𝑖=0
𝑀𝑁𝐹{𝑥[𝑛]} =∑𝑁−1𝑖=0 𝑃𝑆𝐷𝑖𝑓𝑖
∑𝑁−1𝑖=0 𝑃𝑆𝐷𝑖
𝑃𝑆𝐷𝑖
𝑥(𝑡)
𝑃𝑣𝑎𝑟[𝑛] = ∑ 𝑉𝐴𝑅{𝑥[𝑚]}
𝑛
0
𝑉𝐴𝑅{𝑥[𝑛]} = 𝑅𝑀𝑆2− 𝑀𝑉2=1
𝑁∑𝑁−1𝑖=0(𝑋[𝑛] − 𝑀𝑉)2
𝑥(𝑡) −1/𝜋𝑡
𝑖 · 𝑠𝑔𝑛(𝑓) +𝜋/2
−𝜋/2
𝐻𝑇{𝑥[𝑛]} ≡ 𝑋𝐻[𝑛] = ∑𝑥[𝑙] 𝑛 − 𝑙
𝑁−1
𝑙=0
▪
▪
▪
𝑃𝑟𝑒𝑐𝑖𝑠𝑖ó𝑛 = 𝑇𝑃
𝑇𝑃 + 𝑇𝑁 + 𝐹𝑃 + 𝐹𝑁
𝑾
[𝑑 𝑥 𝑘] 𝒙
𝑘 𝑑
𝑥 = [𝑥
1, 𝑥
2, … , 𝑥
𝑑], 𝑥 ∈ ℝ
𝑑↓ 𝒙𝑾, 𝑾 𝑥 ∈ ℝ
𝑑𝑧 = [𝑧
1, 𝑧
2, … , 𝑧
𝑘], 𝑧 ∈ ℝ
𝑘≪ á
á ó
𝑾
𝒛 = 𝒙𝑾 𝑧 ∈ ℝ
𝑘≤
≤ ≥
≤
𝐼𝐺(𝐷𝑝, 𝑓) = 𝐼(𝐷𝑝) − ∑𝑁𝑗 𝑁𝑝 𝐼(𝐷𝑗)
𝑚
𝑗=1
𝑓 𝐷𝑝 𝐷𝑗
𝑗 𝐼 𝑁𝑝
𝑁𝑗 𝑗
(𝐼𝐻)
(𝐼𝐺) (𝐼𝐸)
▪
𝐼𝐻(𝑡) = − ∑ 𝑝(𝑖|𝑡) log2𝑝(𝑖|𝑡)𝑐
𝑖=1
▪ 𝐼𝐺(𝑡) = 1 − ∑ 𝑝(𝑖|𝑡)2
𝑐
𝑖=1
▪ 𝐼𝐸(𝑡) = 1 − max {𝑝(𝑖|𝑡)}
𝑆 = {(𝑥1, 𝑦1), … , (𝑥𝑛, 𝑦𝑛)} 𝑥𝑖∈ ℝ𝑑 𝑦𝑖∈ {+1, −1}
𝐷(𝑥) = (𝑤1𝑥1+ ⋯ + 𝑤𝑑𝑥𝑑) + 𝑏 = < 𝑤, 𝑥 > +𝑏
< 𝑤, 𝑥𝑖> +𝑏 ≥ 0 𝑠𝑖 𝑦𝑖= +1
𝑝𝑎𝑟𝑎 𝑖 = 1, … , 𝑛
< 𝑤, 𝑥𝑖> +𝑏 ≤ 0 𝑠𝑖 𝑦𝑖= −1
𝑦 = 𝑓 (∑ 𝑤
𝑗𝑥
𝑗𝑁
𝑗=1
)
𝑥𝑗
𝑔𝑖(𝑥𝑗) = exp (−∥ 𝑥𝑗− 𝜇𝑖∥2 2𝜎𝑖2 )
𝜇𝑖 𝜎𝑖2
𝐶𝑖)
𝑤𝑖𝑘
𝑦𝑘(𝑥𝑗) = ∑ 𝑤𝑖𝑘𝑔𝑖(𝑥𝑗)
𝑖=0
𝑛ℎ
▪
▪
▪
▪ - -
-
-
-
𝑋
𝑁[𝜇, 𝜎]
𝑥′
𝑃(𝜎 − 𝑥′≤ 𝑋 ≤ 𝜎 + 𝑥′) = ∫ 𝑁[𝜇, 𝜎]𝑑𝑋
𝜎+𝑥′ 𝜎−𝑥′
𝑥′⁄𝜎
1𝜎
𝑁(𝜇, 𝜎) = 1
𝜎√2𝜋𝑒−(𝑥−𝜇)22𝜎2
𝜆
𝛽
𝜆
𝜆
𝜆
𝜆
𝜆
▪
▪
▪
▪
▪
▪
𝑠𝑡𝑑 = √∑𝑛𝑖=1(𝑋𝑖− 𝑋̅)2 (𝑛 − 1)
𝑠𝑡𝑑2= ∑𝑛𝑖=1(𝑋𝑖− 𝑋̅)2 (𝑛 − 1)
𝑐𝑜𝑣(𝑋, 𝑌) =∑𝑛𝑖=1(𝑋𝑖− 𝑋̅)(𝑌𝑖− 𝑌̅) 𝑛 − 1
𝜆 ∈ ℂ 𝑣 ∈ ℂ𝑚, 𝑣 ≠ 0 𝐴𝑣 = 𝜆𝑣
𝑣 𝜆. 𝑣 𝐴
𝜆 𝑣 𝐴
𝜆 𝑣1, 𝑣2 𝜆
𝐴 𝜆
(𝝈) [𝑑 𝑥 𝑑]
𝑐𝑜𝑣(𝒙𝒋 𝒙𝒌)
𝜎𝑗𝑘(𝑥𝑖, 𝑥𝑗) =1
𝑛∑(𝑥𝑗(𝑖)− 𝜇𝑗)(𝑥𝑘(𝑖)− 𝜇𝑘)
𝑛
𝑖=1
, 𝑑𝑜𝑛𝑑𝑒 𝜇 =1 𝑛∑ 𝑥𝑖
𝑖=1
Σ = [ 𝜎
1 2𝜎
12𝜎
21𝜎
2 2]
(𝜆)
Σν = λν
𝜆𝑗
λ
j∑
𝑑𝑗=1𝜆
𝑗𝑾 𝒛,
𝒛 = 𝒙𝑾 𝑧 ∈ ℝ
𝑘▪
▪
▪
𝐸(𝑊, 𝑏) =1
2‖𝑦 − 𝑥‖2 𝑚
𝐸(𝑊, 𝑏) = [1 𝑚∑ (1
2‖𝑦 − 𝑥‖2)
𝑚
𝑖=1
] +𝜆
2 ∑ ∑ ∑ (𝑊𝑖𝑗(𝑙))2
𝑆𝑙+1
𝑗=1 𝑠𝑙
𝑖=1 𝑛𝑙−1
𝑙=1
𝜆
𝑊, 𝑏 𝑊𝑖𝑗(𝑙)= 𝑊𝑖𝑗(𝑙)− 𝛼 𝜕
𝜕𝑊𝑖𝑗(𝑙)𝐸(𝑊, 𝑏) 𝑏(𝑙)= 𝑏(𝑙)− 𝛼 𝜕
𝜕𝑏(𝑙)
𝐸(𝑊, 𝑏) 𝛼
𝜕
𝜕𝑊𝑖𝑗(𝑙)𝐸(𝑊, 𝑏) = [1
𝑚∑ 𝜕
𝜕𝑊𝑖𝑗(𝑙)𝐸(𝑊, 𝑏, 𝑥, 𝑦)
𝑚
𝑖=1
] + 𝜆𝑊𝑖𝑗(𝑙)
𝜕
𝜕𝑏(𝑙)𝐸(𝑊, 𝑏) = 1
𝑚∑ 𝜕
𝜕𝑏(𝑙)𝐸(𝑊, 𝑏, 𝑥, 𝑦)
𝑚
𝑖=1
𝛿𝑜𝑢𝑡 = −(𝑦 − 𝑥)
𝛿𝑙 = ((𝑊(𝑙))𝑇𝛿(𝑙+1)) · 𝑓′(𝑧(𝑙))
𝜕
𝜕𝑊𝑖𝑗(𝑙)𝐸(𝑊, 𝑏, 𝑥, 𝑦) = 𝛿 (𝑙+1)(𝑎(𝑙))𝑇
𝜕
𝜕𝑏(𝑙)𝐸(𝑊, 𝑏, 𝑥, 𝑦) = 𝛿 (𝑙+1)
𝛿𝑗
𝑊(𝑙)= 𝑊(𝑙)− 𝛼 [(1
𝑚Δ𝑊(𝑙)) + 𝜆𝑊(𝑙)]
𝑏(𝑙)= 𝑏(𝑙)− 𝛼 [(1
𝑚Δ𝑏(𝑙) )]
Δ𝑊(𝑙) 𝑦 Δ𝑏(𝑙)
{𝑥1, … , 𝑥𝑁} 𝑁 𝑥
𝜇(𝑗), 𝑗 ∈ {1, … , 𝑘}
𝑑(𝑥, 𝑦)2= ∑(𝑥𝑗− 𝑦𝑗)2
𝑚
𝑗=1
= ∥ 𝑥 − 𝑦 ∥2
𝑆𝑆𝐸 = ∑ ∑ 𝑤(𝑖,𝑗)∥ 𝑥(𝑖)− 𝜇(𝑗)∥2
𝑘
𝑗=1 𝑛
𝑖=1
δj